2005
DOI: 10.1007/s11274-005-8123-3
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Root Surface Colonization Properties of GFP-Tagged Paenibacillus brasilensis PB177

Abstract: This study evaluates the potential of Paenibacillus brasilensis strain PB177 to inhibit phytopathogenic fungi commonly causing maize diseases and to colonize maize plants. In vitro assays demonstrated antagonistic activity against the fungal pathogens, Fusarium moniliforme and Diplodia macrospora. The PB177 strain was tagged with the gfp gene, encoding the green fluorescent protein (GFP) and GFP-tagged bacteria were detected attached to maize roots by stereo-and confocal microscopy. The GFP-tagged bacteria wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…However, the instability of plasmid pHAPII in the transformant limited its usefulness in long-term experiments. Some researchers have reported that the plasmid was stably maintained for several months in the transformants without selection (Njoloma et al 2006;Timmusk et al 2005), while others demonstrated that the plasmid was lost even within several days without antibiotic selection (von der Weid et al 2005). Thus, different strains and plasmids may show different plasmid maintenance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the instability of plasmid pHAPII in the transformant limited its usefulness in long-term experiments. Some researchers have reported that the plasmid was stably maintained for several months in the transformants without selection (Njoloma et al 2006;Timmusk et al 2005), while others demonstrated that the plasmid was lost even within several days without antibiotic selection (von der Weid et al 2005). Thus, different strains and plasmids may show different plasmid maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that bacteria could colonize plant surfaces, such as roots and leaves, often by forming aggregates or microcolonies (Assmus et al 1995;Dandurand et al 1997;von der Weid et al 2005). Different biocontrol strains are known to colonize different regions of plants (Tombolini et al 1999;Ramos et al 2000;Walker et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, visualization methods, such as dual-channel imaging (Bernhardt et al 1999), allow the rapid detection of regulatory networks which are induced by environmental changes, by combining autoradiography and a silver-stained electropherogram (see below). Because of the above, two-dimensional gel electrophoresis has become a very powerful tool to resolve proteins, which are the final stage of gene expression (Volker and Hecker 2005). However, this method is incomplete because the routine analysis does not enable the analysis of several groups of proteins: membrane proteins, highly alkaline proteins, and rare proteins.…”
Section: Proteome Analysismentioning
confidence: 99%
“…They have been reported to be well equipped with Plant Growth promoting (PGP) properties like fixation of nitrogen (Von Der Weid et al 2002), and production of auxins (Lebuhn et al 1997;Bent et al 2001;Da Mota et al 2008) and cytokinin . Bacillus strains have also been reported widely for their ability to suppress pathogens (Von Der Weid et al 2005) and increase the resistance of the plant against diseases (Timmusk and Wagner 1999). Bacillus species with endophytic origin can thus offer highly promising agronomical application as plant probiotics and their long term survival in the host is of great significance to be exploited.…”
Section: Introductionmentioning
confidence: 99%